Expression and purification of soluble bacterially-expressed human hexokinase II in E.coli system - Tanbin, Suriyea; Ahmad Fuad, Fazia Adyani (Association for Computing Machinery, 2019)
Human hexokinase II (HKII) is one of the key enzymes in the glycolytic pathway. It has been postulated that HKII is a potential target for anti-dengue (DENV) drug development, as well as involved in cancer and tumor cell growth. In this work, the human hexokinase II (HKII) gene was cloned into pETite N-His SUMO vector and transformed into the E.coli strain HI-control 10G for the propagation of clones. Two different expression hosts, E.coli HI-controlTM BL21 (DE3) and BL21 (DE3) pLysS were used to optimize HKII expression. In order to obtain the soluble recombinant HKII in a functional form, we optimized protein expression at three different temperatures; 17°C, 25°C and 37°C, at 24 hours incubation time. The soluble protein was expressed in the presence of 0.5 mM isopropyl-2-Dthiogalactopyranoside (IPTG) in TB media at 17°C for 24 hrs. The expressed protein was then purified to homogeneity by a combination of Immobilized Metal Ion Affinity Chromatography (IMAC), size exclusion chromatography (SEC) and ion-exchange chromatography (IEX), resulting in pure bacterially-expressed HK2. Taken together, this study has successfully produced soluble bacterially-expressed human HKII that can be utilized for further therapeutic studies.